THE IMPORTANCE OF SARA PAREEKSHA IN AYURVEDA - A CONCEPTUAL REVIEW - K, Pradeep (AYUSHDHARA, 2017)
Sara concept is related with excellence of Dhatus. Owing to the unending transformations or Paka taking place in the body, Dhatus also differentiate in to Sara bhaga and Kitta bhaga, the ratio of which vary individually. As far as treatment is concerned Sara pareeksha is very important. The conceptual review of this Sara, its relationship with Agni, Prakriti, Bala, and how Sara is related with food intake etc. is done here. it is quite clear that inherent power of a person cannot be assessed by bulk and size of the body, but it is only judged by the Sara examination. Individuals on the basis of Sara have been classified into various categories depending upon the predominance and quality of particular Dhatu in the body, except the Satva Sara which is based on predominance of Satva (psychic factor) in the body. Examination of the Sarata of Dhatu is helpful for the preventive and curative aspect i.e. the Dhatu which is of weak quality in an individual, may be treated with good diet to increase the strength of that Dhatu. Acharya Charaka has also described that the individual having the excellence of all Dhatus (Sarva Sara) have great strength, happiness, resistance to difficulties, self confidence in all enterprises, virtuous acts, and firm and well-built body, correct gait, resonant melodious and high pitched voice, happiness, power, wealth, enjoyment, honour, slowness of aging process, resistance to diseases, having more progeny and longevity. For determining the Datusarata, when the positive features are present above 60%, it will be considered as best quality (Pravara sarata). When the positive features are present between 59% and 50%, it will be considered as moderate tissue quality (Madhyam Sarata). When the positive features are present between 49 to 35%, it will be labelled as poor tissue quality (Heena Sarata).